PENGUKURAN pH, DISSOLVED OXYGEN (DO), DAN TOTAL DISSOLVED SOLID (TDS) PADA SUNGAI WILAYAH INDUSTRI COR LOGAM KABUPATEN HULU SUNGAI SELATAN - Kartini, Kartini; Rizani, Ahmad; Fajar, Reza Adhi; Saptarini, Dessy Lestari; Rizhan, Muhammad (Universitas Lambung Mangkurat, 2024)
Water is essential for human life, used daily for drinking, cooking, bathing, washing, and various other purposes. The presence of industrial waste can significantly impact the water quality of rivers located in industrial areas. In North Daha District, South Kalimantan, there is a metal casting industry that discharges its waste into a nearby river. Therefore, measuring the water quality of the river is necessary to determine the level of pollution caused by industrial waste. The objective of this study is to obtain parameters from water quality tests, such as pH, dissolved oxygen (DO), and total dissolved solid (TDS), to assess the river's condition before and after metal casting processed. Additionally, the study aims to compare the test results against water quality standards for public consumption. The research method involves direct measurement of river water using a multiparameter water quality testing instrument. The test results before metal casting processed are pH 6,33 – 6,47; DO 1,03 – 2,18 ppm; and TDS 45 – 65 ppm. The test result after casting processed are pH 6,57 – 6,85; DO 6,66 – 13,19 ppm; and TDS 43 – 48 ppm. Comparing from PP RI Number 82 (2001) that the metal casting industry activities have water criterion within the range allowable values. That indicate the industry do not contaminate the river in the industrial area. The river pollution is primarily caused by tidal phenomena, particularly during low tide conditions.